FTIR, 13C NMR, and GPC analysis of high‐propylene content co‐ and terpolymers with ethylene and higher α‐olefins synthesized with EtInd2ZrCl2/MAO - Ferreira, María Luján (2001)
This article reports the results of propylene/alfa-oleﬁn copolymerization and propylene/ethylene/alfa-oleﬁn terpolymerization using low concentrations(less than 5 mol %) of long alfa-oleﬁns such as 1-octene, 1-decene, and 1-dodecene. Kinetics data are presented and discussed. The highest activity was found with the longest alfa-oleﬁn studied (1-dodecene). A possible explanation is proposed for this and other characteristics of the polymers obtained. The effect of low-ethylene contents (4 mol% in the gas phase) on the copolymerization of propylene/alfa-oleﬁns was also examined. The polymers synthesized were characterized by 13CNMR, gel permeation chromatography, DSC, Fourier transform infrared spectroscopy, and wide-angle X-ray scattering.